Consumption tendencies of foods of animal origin in Hungary - Balogh, Viktória (Acta Agraria Debreceniensis, 2009)
One of the most important indices of the population's food consumption are the quantities of the consumed foods expressed in a natural measure. In the course of my examination from the 1980 years I examined how our dietary habits changed. I was able to demonstrate it by the time series examination well, in which years and in a what kind of measure these consumer changes occurred. The trend analysis was in it onto my help, that let me be allowed to depict his beat as the changes of the food consumption visual.In his totality the Hungarian population nutritional and from his consumer customs we may relate that the present nourishment increases it unambiguous the diet pendant the risk of illnesses, furthers their development, aggravates their effect, and contributes to the population's adverse health conditions powerful.It was over in some years, in a decade on a unfortunate manner, we lost the natural instinct of the selection of the food in a considerable part. Our diet fundamental the narrower and the customs of wider environment, his rules, the social values, beliefs define it. Because of this to feed it is necessary to study it.The changed and the health-conscious nourishment would be  important for him herding back into a upturned dietary habit correct bed with a wide circle recognizing him with the population, his role could be big for the healthy, or functional foods. The nourishment gives his pleasure likewise while we take over healthy foods.The recognition of the changes of the demand and accompanying him with attention could be the domestic food producers' fundamental interests. The consumer types and the market segments should be mapped, that they suitable marketing a strategy can be aimed at it, and into the direction of the healthy nutrition to push away, and would be need onto an efficient informative campaign, onto an advertisement message formulated well, onto the making aware of this, that let the advertisement supply an educational function in one.